Plant Pathogenic Microorganisms: State-of-the-Art Research in Spain (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Pathogenic microorganisms, including fungi, oomycetes, bacteria, viruses, and viroids, constitute a serious threat to agriculture worldwide. In Spain, one of the countries with the highest proportion of agricultural gross domestic product in Europe, the agri-food industry is the main manufacturing activity. Consequently, the presence and emergence of microorganisms causing serious plant diseases to economically important crops is especially relevant. In line with this, Spain has an important number of research groups interested in plant pathology, with scientists working on many aspects of pathogenic microorganism–plant interactions, from the basic aspects to more applied studies. In recent years, numerous important advancements have been achieved by scientists working in Spain in terms of the biological and molecular characterization of plant pathogenic microorganisms, in elucidating mechanisms of microbe pathogenesis, plant resistance to microbe infection, and plant–microbe–vector interactions. All these new achievements have provided essential knowledge for agricultural researchers worldwide.The aim of this Special Issue was to provide a platform for Spanish researchers interested in plant pathogenic microorganisms to share their recent results related to microbe–plant host interactions, microbe–vector interactions, microbe–microbe interactions, evolution, ecology, and control strategies.